A proposed model for applying the Analytical Procedures Auditing Standard (No. 520) to measure the creditworthiness of customers (Applied to Alawwal Medical Laboratories customer account balances for the year 2021) - Abdalrahim, Alfateh Alamin; Elhadi, AbdElhaq Maki (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to try to develop a scientific framework that would enable auditors to use Auditing Standard No. 520 for analytical procedures to determine the creditworthiness of customers and to identify the impact of applying Auditing Standard No. 520 for analytical procedures on classifying customers according to different levels of creditworthiness. To achieve the objectives of the study, a descriptive approach was used. The analytical population was commercial and service institutions, while the study sample represented the service sector as applied to Alawwal Medical Laboratories. The reason for choosing Alawwal Medical Laboratories is that they represent an important group from the service sector segment spread across many branches in the Kingdom of Saudi Arabia. As a primary tool for collecting data, a group of clients of the First Medical Laboratory was obtained, and the review standard No. 520 for analytical procedures was applied to them. The study reached many results, including: Applying the review standard No. 520 contributes to classifying clients into different levels of creditworthiness, enabling the auditor to And credit management both enable appropriate decision-making. Applying Auditing Standard No. 520 for analytical procedures contributes to developing early indicators that warn of the presence of customers with a low creditworthiness rating, and then the auditor uses other review programs for the customer item, such as obtaining approvals for customers with low creditworthiness.